Assessment of Bacterial Community Composition and Dynamics in Alfalfa Silages With and Without Lactobacillus plantarum Inoculation Using Absolute Quantification 16S rRNA Sequencing - Yang, Fengyuan; Zhao, Shanshan; Wang, Yuan; Fan, Xiaomiao; Wang, Yanping; Feng, Changsong (Frontiers in Microbiology, 2021)
Relative quantification 16S-seq (RQS) has drew deeper insights into bacterial community compositions in silage. However, it provides no information on dynamics of the total amount of bacterial DNA through the ensiling process and across different treatments. In this study, bacterial compositions in alfalfa silage with and without Lactobacillus plantarum inoculation after 10 and 60 d of ensiling were investigated using absolute quantification 16S-seq (AQS), and bacterial composition and its interaction with fermentation properties of silage indicated by AQS and RQS were compared. Variation in total bacterial DNA amounts across different treatments and ensiling periods was illustrated by AQS. AQS indicated higher bacterial richness indices and closer correlations of these indices with fermentation properties than RQS via spearman’s correlation analyses, as well as more taxa with significance on bacterial abundance via lefse analyses. In conclusion, AQS effectively illustrated the dynamics of bacterial communities during the ensiling process.